MODEL SISTEM INFORMASI PROTEKSI SERTA PENGASUTAN DAN PENGHENTIAN MOTOR INDUKSI TIGA FASE DENGAN MENGUNAKAN SMS - Adriani Adriani (VERTEX ELEKTRO, 2020)
As well as the Protection of Information System Models  Starting And Penhentian Mi3f By Using Sms. PLC (programmable logic control) is a device (equipment) that is used to  replace the sequential relay circuits to control the machine. The research method ology used in  the preparation of this final project is besifat experimental study using SMS as a media object to  detect an error in an induction motor. The protection of information systems using the  instrument for the identification of disorders includes two types: overcurrent relays and current  sensors for detecting large flows entering and phase detection in case of failure.